Faktor Berhubungan dengan Rendahnya Kunjungan Antenatal pada Kontak Pertama Pemeriksaan Ibu Hamil (K-1) - Dengo, Moh. Rivandi; Mohamad, Idjrak (Universitas Gorontalo, 2019)
The coverage of Antenatal Care (ANC) visits in Gorontalo District during the last three years is as follows: the first visit of the pregnant women in 2015 reached 90%, the visit in the following year in 2016 decreased to 76%, and the visit in 2017 reached 89,86%. This research aims to find out the factors related to the decrease of Antenatal Care in accordance with the decrease in the Antenatal Care visits in the first contact of pregnant women checking K-1 in the working area of Community Health Center Bongomeme Gorontalo District in 2018. The population of the current research was all pregnant women listed in Kohort pregnant women book in the Community Health Center Bogomeme in 2018 there were 163 pregnant women participated. The research design used was a cross sectional study approach. The obtained data were subsequently examined using chi-square test by referring to p value < 0,005. The research results shown that the parity variable of the pregnancy has p value of 0,038, pregnant women knowledge has p value of 0,012, and pregnant women job has p value of 0,000. Thus, this variable has a parity of pregnancy, knowledge of pregnant women and occupation of pregnant women has a relationship with antenatal visits (K-1), while family support variables with p value of 0.478 means that this variable has no relationship with antenatal visits (K-1). The conclusion was the parity, pregnant women knowledge, and pregnant women occupation have the significant relationship with the antenatal care visits (K-1), while the family support has no significant relationship with antenatal visits (K-1). The pregnant women should maintain the pregnancy spacing, maintain the pregnancy health, and increase their knowledge.Cakupan kunjungan Antenatal Care (ANC) di Kabupaten Gorontalo selama tiga tahun terakhir adalah cakupan kunjungan pertama ibu hamil (K-1) tahun 2015 mencapai 90%, pada tahun berikutnya tahun 2016 terjadi penurunan yaitu 76% dan pada tahun 2017 mencapai 89,86%. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan rendahnya kunjungan Antenatal Care pada kontak pertama pemeriksaan ibu hamil K-1 pada Wilayah Kerja Puskesmas Bongomeme Kabupaten Gorontalo tahun 2018. Adapun populasi pada penelitian ini adalah seluruh ibu hamil tercatat di buku kohort ibu hamil Puskesmas Bongomeme tahun 2018 yaitu sebanyak 163 orang ibu hamil. Desain penelitian yang digunakan adalah pendekatan cross sectional study. Data yang diperoleh kemudian dilakukan uji statistic chi square dengan melihat nilai p value < 0,005. Hasil penelitian menunjukkan bahwa variable paritas kehamilan dengan nilai p value 0,038, pengetahuan ibu hamil nilai p value 0,012, dan pekerjaan ibu hamil nilai p value 0,000. Artinya variabel paritas kehamilan, pengetahuan ibu hamil dan pekerjaan ibu hamil memiliki hubungan dengan kunjungan antenatal (K-1). Sedangkan variabel dukungan keluarga nilai p value 0,478 ini berarti variabel dukungan keluarga tidak memiliki hubungan dengan kunjungan antenatal (K-1). Disimpulkan bahwa paritas, pengetahuan ibu, pekerjaan ibu ada hubungan yang signifikan dengan kunjungan antenatal K-I, sedangkan dukungan keluarga tidak memiliki hubungan yang signifikan dengan kunjungan antenatal (K-I). Ibu hamil agar lebih menjaga jarak kehamilan, menjaga kesehatan kehamilan, meningkatkan pengetahuan ibu hamil.